A simple guide to IBM SPSS statistics for Version 23.0 - Kirkpatrick, Lee A. 1958-; Feeney, Brooke C. 1969- (Cencage Learning, 2016)
This no-nonsense book teaches you everything you need to know about the newest version of SPSS for Windows so you can effectively use the program in your statistics class. The guide's simple, straightforward style frees you to concentrate on learning basic statistical concepts, while still developing familiarity with SPSS. In no time, you will be using SPSS to do homework problems and conduct statistical analyses for research projects